2023
DOI: 10.1037/tra0001116
|View full text |Cite
|
Sign up to set email alerts
|

Social support and prolonged grief disorder symptoms in parents who lost their only child from urban and rural China.

Abstract: Objective: The one-child policy has existed in China for more than 30 years. It brought benefits to the country's economic development and reduced the magnitude of the population within a short period. However, it has led to the emergence of a significant number of parents who have lost their only child, referred to as shiduers (失独者). This study explored the symptoms of prolonged grief disorder (PGD) among shiduers and their relationship with the social support shiduers received after they lost the child, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Social support may also help individuals cope with PGD. Song et al [42] found PGD symptoms of Shidu parents were negatively correlated with social support. The study in caregivers of people with motor neurone disease revealed social support was a critical predictive factor of PGD, and increasing social support could reduce psychological distress [16].…”
Section: The Moderating Role Of Social Supportmentioning
confidence: 99%
“…Social support may also help individuals cope with PGD. Song et al [42] found PGD symptoms of Shidu parents were negatively correlated with social support. The study in caregivers of people with motor neurone disease revealed social support was a critical predictive factor of PGD, and increasing social support could reduce psychological distress [16].…”
Section: The Moderating Role Of Social Supportmentioning
confidence: 99%